2014
DOI: 10.3390/en7095502
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Analysis of Transport Processes and Efficiency of Combined SOFC and PEMFC Systems

Abstract: A hybrid fuel cell system (~10 kWe) for an average family house including heating is proposed. The investigated system comprises a Solid Oxide Fuel Cell (SOFC) on top of a Polymer Electrolyte Fuel Cell (PEFC). Hydrogen produced from the off-gases of the SOFC can be fed directly to the PEFC. Simulations for the proposed system were conducted using different fuels. Here, results for natural gas (NG), dimethyl ether (DME) and ethanol as a fuel are presented and analysed. Behaviour of the proposed system is furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 32 publications
(35 reference statements)
0
9
0
Order By: Relevance
“…These models range from zero-dimensional (0-D) ones, which are lumped models using concentrated parameters and which can only relate to cell global proprieties, to three dimensional (3-D) ones, which are detailed models using distributed parameters and can describe cell local proprieties on the three spatial coordinates. The use of any one of these types of models depends of the research aims: Usually 3-D and 2-D models concern phenomena investigation, while 1-D and 0-D models are related to control purposes [6][7][8][9][10][11].…”
mentioning
confidence: 99%
“…These models range from zero-dimensional (0-D) ones, which are lumped models using concentrated parameters and which can only relate to cell global proprieties, to three dimensional (3-D) ones, which are detailed models using distributed parameters and can describe cell local proprieties on the three spatial coordinates. The use of any one of these types of models depends of the research aims: Usually 3-D and 2-D models concern phenomena investigation, while 1-D and 0-D models are related to control purposes [6][7][8][9][10][11].…”
mentioning
confidence: 99%
“…In the current model, the fuel was converted into carbon monoxide and hydrogen prior to the SOFC through partial oxidation. Partial oxidation is considered in this study because it makes use of air, which can be an advantage for mobile applications [26]. The reformer model aims at determining the amount of fuel in mol (mol fuel_FC ) and the heat energy required by the system, considering the stoichiometric reactions of the partial oxidation.…”
Section: Reformer Unitmentioning
confidence: 99%
“…Most of the studies found in the literature used the fuel cell as the sole prime mover in the cogeneration system. Only several studies combined between two types of fuel cell [25,26,28,57,61,62] and the combinations between the fuel cell and other energy conversion devices such as photovoltaic, electrolyzer, thermoelectric and batteries as the storage were reported in [46,[63][64][65].…”
Section: Summary Of the Gathered Literature In The Past 5 Yearsmentioning
confidence: 99%